Regional inequality and internal conflict - Christian Lessmann (Center for Economic Studies and ifo Institute (CESifo), 2013)
This paper studies the influence of interregional inequality within countries on internal con-flicts. Regional inequalities are measured by the population-weighted coefficient of variation of regional GDP per capita. As the main innovation, I use a panel data set of country-level re- gional inequalities, which covers 56 countries (835 subnational regions) between 1980 and 2009. I also consider a broader cross-section data set for the year 2005, which covers 110 countries (1569 subnational regions). Conflict is measured by the incidence of civil war (UCDP/PRIO data) and a risk measure of internal conflict (war, terrorism, and riots) provided by the PRS Group's International Country Risk Guide. Logit estimations are employed as well as OLS fixed effects panel regressions. I find that regional inequalities increase the risk of internal conflict.
Keywords: D63; D74; O15; R12; 330; regional inequality; internal conflict; panel data